Quality Analysis of The Road Widening Project Towards Standards for The Grobogan Road Section - Jember District Limit (Link. 199) - Christabella, Cynthia Cielly; Putra, I Nyoman Dita Pahang (Universitas Negeri Padang, 2024)
Roads are a land transportation route that has been used since ancient times as a means for people to move places using existing transportation. In road construction efforts, it is necessary to have Standard Operating Procedures, or SOPs, that are used with the aim of improving worker performance, ensuring road quality, increasing profits, and company development. SOP is a method or work flow that has been standardized, is used as binding and directive instructions, and covers things from an activity that has steps or procedures. Currently, there are still many road work projects that are carried out without paying attention to existing SOPs, and this means that the quality of the concrete roads being made does not comply with applicable standards, which means that some parties may experience losses. There needs to be a good understanding of how SOPs comply with standards so that they can produce concrete of maximum quality. This writing was prepared using an analytical method using a literature study that refers to the Indonesian National Standards (SNI) and the PUPR Ministerial Regulation (Regulation of the Minister of Public Works and Public Housing).